Management of intellectual property in the development of cultural industry in Hanoi city - Thi Phuong Oanh, Nguyen; Tung Son, Le (VNU Journal of Science: Policy and Management Studies, 2023)
Intellectual property management in the development of the cultural industry plays an important role in realizing the goals in the documents of the Hanoi Party Committee on the development of the cultural industry by 2025, with orientations to 2030 and vision to 2045. By qualitative research method combined with quantitative research, analyze and point out: 03 problems posed in perfecting the intellectual property management model in Hanoi to cultural industry development. The study proposes the construction of an intellectual property management model based on the formation of a link between state management agencies and social organizations, with the core being the Collective Managerment of copyright and Related rights and intellectual property owners to manage intellectual property in order to develop the cultural industry in Hanoi.